2016
DOI: 10.15403/jgld.2014.1121.253.rc2
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 2 Signalling and the Lysosomal Machinery in Barrett’s Esophagus

Abstract: Background & Aims: Inflammation plays an important role in the development of esophageal adenocarcinoma and its metaplastic precursor lesion, Barrett’s esophagus. Toll-like receptor (TLR) 2 signalling and lysosomal function have been linked to inflammation-associated carcinogenesis. We examined the expression of TLR2 in the esophagus and the effect of long-term TLR2 activation on morphological changes and expression of factors involved in lysosomal function in a Barrett’s esophagus epithelium cell line.&#x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Both primary esophageal epithelial cells and the EPC2‐hTERT cell line express TLR1 through TLR6 , with minimal expression of TLR7 through TLR10, CD14, and CLEC7A. As in prior studies, we observe robust mRNA expression of TLR2 and TLR3 . We did not observe significant differences in PRR expression between cell lines from EoE patients and controls (Figure A).…”
Section: Resultssupporting
confidence: 80%
“…Both primary esophageal epithelial cells and the EPC2‐hTERT cell line express TLR1 through TLR6 , with minimal expression of TLR7 through TLR10, CD14, and CLEC7A. As in prior studies, we observe robust mRNA expression of TLR2 and TLR3 . We did not observe significant differences in PRR expression between cell lines from EoE patients and controls (Figure A).…”
Section: Resultssupporting
confidence: 80%
“…Our study showed predominantly superficial increase in TLR2 expression in reflux oesophagitis. The increase in TLR2 expression was consistent with the general pattern reported for TLR2 in inflammatory conditions [23,24] and also with a study from Verbeek et al [25], who showed that TLR2 mRNA expression increased non-significantly in reflux oesophagitis. The shift to more superficial distribution of TLR2 suggests that luminal TLR2 ligands might play a role in GERD pathogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…First, alteration of the microbiota may result in inflammation, and persistent chronic inflammation may promote carcinogenesis[71]. The disequilibrium between human immunity and microbiota may change the compositions of essential bacterial molecules at certain organs or sites and then form microorganism-associated molecular patterns (MAMPs)[71], such as toll-like receptors (TLRs) and nucleotide-binding-oligomerization-domain (NOD)-like receptors[72,73]. Then, the subsequent activation of related pathways may lead to the production and release of some target genes involved in inflammation[73], such as cytokines, chemokines and other inflammatory factors.…”
Section: Mechanismsmentioning
confidence: 99%